2022
DOI: 10.1371/journal.pgph.0000315
|View full text |Cite
|
Sign up to set email alerts
|

Status of psychological health of students following the extended university closure in Bangladesh: Results from a web-based cross-sectional study

Abstract: Students’ severe affective mental distress has emerged as significant public health attention globally because of the disastrous effects of coronavirus disease 2019 (COVID-19). The current study aimed at exploring the prevalence of two alarming psychological distresses, depression and anxiety, among university students following a prolonged shutdown of educational institutions in Bangladesh. A cross-sectional online-based study was conducted by deploying two standard scales to assess the depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…[28][29][30][31][32][33] The impact of COVID-19 pandemic and its responses is tremendous on human life across the world. 8,[34][35][36][37][38][39][40][41][42][43][44][45] Therefore, along with COVID-19 vaccines, people in poor and developing countries might consume a myriad of antibiotics and other drugs without prescription during the COVID-19 waves. [46][47][48][49][50][51][52][53][54][55] The lessons learned from the previous pandemic should be implemented to regulate the usage of antibiotics in these countries.…”
mentioning
confidence: 99%
“…[28][29][30][31][32][33] The impact of COVID-19 pandemic and its responses is tremendous on human life across the world. 8,[34][35][36][37][38][39][40][41][42][43][44][45] Therefore, along with COVID-19 vaccines, people in poor and developing countries might consume a myriad of antibiotics and other drugs without prescription during the COVID-19 waves. [46][47][48][49][50][51][52][53][54][55] The lessons learned from the previous pandemic should be implemented to regulate the usage of antibiotics in these countries.…”
mentioning
confidence: 99%
“… 46 , 47 , 48 , 49 , 50 , 51 , 52 Students are sometimes unable to participate in face‐to‐face communication since they need to attend an online class. 53 , 54 , 55 This increased involvement of students in the digital world may contribute to the growth of PIU. 56 , 57 A study observed that school‐going adolescents involved more with the internet (e.g., gaming, talking, or streaming videos) are more likely to develop depressive symptoms because they are subjected to unrealistic depictions of others.…”
Section: Discussionmentioning
confidence: 99%
“…The lockdown due to COVID‐19 has increased students' engagement with internet use 46–52 . Students are sometimes unable to participate in face‐to‐face communication since they need to attend an online class 53–55 . This increased involvement of students in the digital world may contribute to the growth of PIU 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Bangladesh has closed all of its educational institutions since March 17 th , 2020. Incoming flights from European destinations are likewise forbidden initially 57 . To curb the spread of the virus, Bangladesh has also banned all international commercial passenger flights with other nations multiple times.…”
Section: Effect Of Covid-19 On Daily Life Of Bangladeshmentioning
confidence: 99%